Application of Resampling Techniques to the Statistical Analysis of the Brier Score - Ikeda, M.; Itoh, S.; Ishigaki, T.; Yamauchi, K. (Methods of Information in Medicine, 2001)
We investigated the application of resampling techniques to the statistical analysis of the Brier score (B), and extended them to the statistical comparison of two Bs derived from the same set of patients. The re-sampling techniques are helpful in the statistical analysis of B, and there are almost no differences between the jackknife method and the bootstrap method in this analysis. Thus, we believe that B should be used more often as an index to evaluate probabilistic judgments in the case in which the data sets for the assessment are “degenerate” as the “receiver operating characteristic data sets.”
Keywords: Brier Score; Resampling; Jackknife; Bootstrap; Observer Performance Study